Efficacy of kinesio tape on neck pain and functional disability in pregnant women: a randomized controlled trial - EmanA. Elhosary; MahmoudM. Ewidea; MarwaA. Mohamed (Clinical and Experimental Obstetrics & Gynecology)
Neck pain during pregnancy has negative effects on the quality of a woman’s life. The goal of this study was to determine the efficacy of kinesio-tape application on neck pain and functional activity during pregnancy. Thirty primigravid women who suffered from mechanical neck pain during the second and third trimester of pregnancy were recruited. They were randomly assigned to two groups: one received general antenatal advice about good posture in addition to kinesio taping for 4 weeks; the other received only general antenatal advice about good posture. Pain was assessed with the Visual Analogue Scale (VAS) and Neck Disability Index scale (NDI) at the start of the study and after 4 weeks of treatment. After 4 weeks, both groups showed improvement, but the group that received advice and kinesiology taping showed significantly less pain (VAS) than did the control group, but no differences in NDI scores. Kinesiology taping and antenatal advice are more effective for treatment of neck pain during pregnancy than is antenatal advice alone.